Analysis and Optimization of LoRa SX1278 Ra-02 Transmission Performance for an Internet of Things-Based Water Quality Monitoring System: Analisis dan Optimasi Kinerja Transmisi LoRa SX1278 Ra-02 untuk Sistem Monitoring Kualitas Air Berbasis Internet of Things - Isa Mahfudi; Farida Arinie Soelistianto; Adinda Aditya; Yossy Dwi Meylinda (Universitas Muhammadiyah Purwokerto, 2026)
Water quality is a critical indicator of environmental health, yet conventional monitoring methods remain limited in coverage and efficiency. To address these limitations, this study proposes an Internet of Things (IoT)-based water quality monitoring system employing long-range communication using the LoRa SX1278 module, with the objective of analyzing the influence of LoRa physical parameters and determining the most optimal transmission configuration for field monitoring applications. The experimental method involved varying the Spreading Factor, Bandwidth, Coding Rate, and Transmit Power, while transmission performance was evaluated based on RSSI, SNR, Packet Delivery Ratio (PDR), and delay, with sensor data transmitted in real time to the ThingSpeak platform for visualization and validation. The results indicate that the configuration SF9–BW125 kHz–CR4/7–TxPower +14 dBm provides the best overall performance, achieving a PDR of 96–98%, a delay of 380–410 ms, and a power consumption of 82 mA; moreover, field testing demonstrated stable system operation up to 300 meters under Line-of-Sight (LOS) conditions and up to 200 meters under Non-Line-of-Sight (NLOS) conditions. These findings highlight that appropriate LoRa parameter tuning significantly enhances range, reliability, and energy efficiency, making the proposed configuration the optimal choice for IoT-based water quality monitoring systems requiring long-range, reliable, and low-power communication. ABSTRAK (Bahasa Indonesia) Kualitas air merupakan indikator penting bagi kesehatan lingkungan, namun pemantauan secara konvensional masih terbatas dalam jangkauan dan efisiensi. Untuk mengatasi kendala tersebut, penelitian ini mengusulkan sistem monitoring kualitas air berbasis Internet of Things (IoT) dengan komunikasi jarak jauh menggunakan LoRa SX1278, dengan tujuan menganalisis pengaruh parameter fisik LoRa serta menentukan konfigurasi transmisi yang paling optimal untuk pemantauan kualitas air di lapangan. Metode yang digunakan adalah eksperimen dengan memvariasikan Spreading Factor, Bandwidth, Coding Rate, dan Transmit Power, sedangkan kinerja transmisi dievaluasi berdasarkan RSSI, SNR, Packet Delivery Ratio (PDR), dan delay, dengan data sensor dikirim secara real-time ke platform ThingSpeak untuk visualisasi dan validasi. Hasil penelitian menunjukkan bahwa konfigurasi SF9–BW125 kHz–CR4/7–TxPower +14 dBm memberikan performa terbaik dengan PDR 96–98%, delay 380–410 ms, dan konsumsi daya 82 mA; sementara pengujian lapangan menunjukkan sistem mampu beroperasi stabil hingga 300 meter pada kondisi LOS dan hingga 200 meter pada kondisi NLOS. Hasil ini menegaskan bahwa pengaturan parameter LoRa yang tepat mampu meningkatkan jangkauan, reliabilitas, dan efisiensi energi, sehingga konfigurasi tersebut direkomendasikan sebagai pengaturan optimal untuk sistem monitoring kualitas air berbasis IoT yang membutuhkan komunikasi jarak jauh yang andal dan hemat daya.